Genomic Characterization of mcr-1.1-Producing Escherichia coli Recovered From Human Infections in São Paulo, Brazil - Girardello, Raquel; Piroupo, Carlos Morais; Martins, Joaquim; Maffucci, Marcia Helena; Cury, Ana Paula; Franco, Maria Renata Gomes; Malta, Fernanda de Mello; Rocha, Natália Conceição; Pinho, João Renato Rebello; Rossi, Flavia; Duarte, Alberto José da Silva; Setubal, João Carlos (Frontiers in Microbiology, 2021)
Polymyxins are one of most important antibiotics available for multidrug-resistant Gram-negative infections. Diverse chromosomal resistance mechanisms have been described, but the polymyxin resistance phenotype is not yet completely understood. The objective of this study was to characterize colistin resistant mcr-1-producing strains isolated from human infections over one year in a hospital setting (Hospital das Clínicas, São Paulo, Brazil). We isolated 490 colistin-resistant Gram-negative rods, of which eight were mcr-1.1 positive E. coli, the only specie with this result, indicating a low incidence of the mcr-1 production mechanism among colistin-resistant isolates. All mcr-1.1 positive isolates showed similar low MICs for colistin and were susceptible to most antibiotics tested. The isolates showed diversity of PFGE fingerprints and MLST classification. In most isolates the mcr-1.1 gene was located in an IncX4 plasmid. The eight mcr-1.1-positive E. coli genomes were sequenced. Three different genomic contexts for mcr-1.1 were observed, including a genomic cassette mcr-1.1-pap2 disrupting a DUF2806 domain-containing gene in six isolates. In addition, an IS1-family transposase was found inserted into the mcr-1.1 cassette in one isolate. A single mcr-1.1-pap2 genomic cassette was identified in another isolate. Our results suggest that clonal dissemination of hospital-resident strains took place during the study period, and that, in addition, strains are also coming from the outside, possibly in patients’ microbiota. Genomic sequencing was essential to distinguish these two sources.